Exploring the Benefits of Kusir as a Complementary Effort to Alleviate Fluor Albus in Adolescent Girls - Yeni Nur Sa’diyah; Dwi Riyan Ariestantia (Newinera Publisher, 2025)
Fluor albus or vaginal discharge is a common reproductive health problem among adolescent girls. When abnormal, it can interfere with daily activities, cause discomfort, and potentially lead to more serious health issues if left untreated. Despite this, many adolescents are reluctant to report symptoms to parents or health professionals because the issue is considered sensitive. This situation highlights the need for safe, acceptable, and effective complementary therapies to manage fluor albus in adolescents. This study aimed to examine the effectiveness of the traditional herbal medicine KUSIR, made from turmeric and betel leaf, in reducing the severity of fluor albus among adolescent girls.The study employed a quantitative approach using a quasi-experimental pretest posttest control group design. A total of 64 adolescent girls participated and were divided into an intervention group receiving KUSIR herbal treatment and a control group without intervention. Data were analyzed using the Wilcoxon test to examine changes before and after treatment and the Mann Whitney U test to compare outcomes between groups.The findings showed a clear reduction in the severity of fluor albus in the intervention group compared to the control group. Mann Whitney U analysis indicated a significant difference in posttest scores, with a higher mean rank in the intervention group than in the control group. The Wilcoxon test confirmed that all participants in the intervention group experienced a decrease in symptoms. KUSIR herbal treatment is effective as a complementary therapy for reducing fluor albus severity in adolescent girls. Turmeric and betel leaf offer a natural, affordable, and acceptable alternative for adolescent reproductive health care.